ORIENTASI KEBIJAKAN SISTEM RESI GUDANG DI INDONESIA: SUATU PEMBACAAN DARI PARADIGMA CRITICAL - Zulaekhah, Siti; Suteki, Suteki; Prananingtyas, Paramita (UI Scholars Hub, 2021)
The formation of public policies, including the Warehouse Receipt System in Indonesia, is based on interests, whether sourced from the internalstate or originating from external or other countries environmental factors. Adaptation to external factors cannot be denied because the Indonesian Government has to follow the mechanism that is enforced internationally, mainly in the commercial and financial fields, including banking. This paper aims at analyzing the direction of the warehouse receipt system policy in Indonesia, identifying and describing the policy of the warehouse receipt system and describing it based on the reading of the critical paradigm, and exploring the potential for the development of legal knowledge of the warehouse receipt system policy. The results of the conceptual review of this paper showed that the policy of the Warehouse Receipt System in Indonesia is directed atproviding opportunities to farmers to access credit with savings commodities as collateral.